The origin of the Lithuanian denominative suffix -yti, ‑ija - Villanueva Svensson, Miguel (Baltistica, 2023)
The Baltic denominative suffix Lith. dal-ýti, -ìja, Latv. sàl-ît, -ĩju does not go back to denominatives from i-stems, as generally assumed. It was an offshoot of the Balto-Slavic ī-verbs consisting of the present stem vowel *-i (PIE 3 sg. *prok̑éi̯eti > Bl.-Sl. *praśīti > *praśīt > Bl. *praśī > 3rd person *praśi) + *-i̯a (the universal present stem suffix for denominatives in Baltic). This is in accordance with the development of Balto-Slavic ī-verbs in Baltic.